The Effect of Syringic Acid and Phenoxy Herbicide 4-chloro-2-methylphenoxyacetic acid (MCPA) on Soil, Rhizosphere, and Plant Endosphere Microbiome - Mierzejewska, Elżbieta; Urbaniak, Magdalena; Zagibajło, Katarzyna; Vangronsveld, Jaco; Thijs, Sofie (Frontiers in Plant Science, 2022)
The integration of phytoremediation and biostimulation can improve pollutant removal from the environment. Plant secondary metabolites (PSMs), which are structurally related to xenobiotics, can stimulate the presence of microbial community members, exhibiting specialized functions towards detoxifying and thus mitigating soil toxicity. This In this study we study evaluated the effects of enriching enrichment of MCPA-contaminated soil (unplanted and zucchini-planted) with syringic acid (SA) on the bacterial community structure in soil, the rhizosphere and plantzucchini endosphere. Additionally, we measured the concentration of MCPA in soil and fresh biomass of zucchini. The diversity of bacterial communities differed was significantly different between the studied compartments (i.e. unplanted bulk soil, rhizospheric soil, and plant endosphere: roots or leaves) and in response to the treatments between used treatments (MCPA or/and SA application). The highest diversity indices were observed for unplantedbulk soil and rhizosphere. Although the lowest diversity was observed among leaf endophytes, this community was significantly affected by the amendments: MCPA or SA: the compounds applied separately favoured favoureding the growth of Actinobacteria (especially Pseudarthrobacter), ), while their while ssimultaneous application addition of MCPA+SA promoted the growth of Firmicutes (especially Psychrobacillus). Application of MCPA+SA together Additionally,lead also to MCPA+SA enrichment enhanced growth of Pseudomonas, Burkholderia, Sphingomonas and Pandoraea in the rhizosphere, while SA increased the occurrence of Pseudomonas in leaves. In addition, Adding SA appeared to have a positive ly influence on the degradative potential of the bacterial communities against MCPA: the addition of SA its addition, followed by zucchini planting, significantly increased the removal of MCPA the herbicide (50%) from MCPA-contaminated soil in zucchini planted variants. without affecting, neither positively nor negatively, However, SA did not affectthe plant growth, neither positively nor negatively.